2012
DOI: 10.1071/an11336
|View full text |Cite
|
Sign up to set email alerts
|

Growth and carcass characteristics of crossbred lambs in various production systems

Abstract: Lamb growth, carcass and pelt measurements are reported from 5775 lambs born to Border Leicester × Merino (BLM) and Hyfer (Dorset × Merino composite) ewes joined to Dorset, Suffolk and Hyfer rams in three lamb-production systems at Cowra and Wagga Wagga over 5 years. The production systems involved lambings at different seasons of the year and increasing levels of intensification from autumn annual joining, spring joining with a backup mating for non-pregnant ewes, to an accelerated 8-monthly lambing system. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The higher growth rates in ram lambs observed in the present study agree with the growth rates found by Lee (1986a) . The 15% higher ADG for ram compared with wether lambs is in close agreement with the results of the studies of Fogarty and Mulholland (2012) and Fogarty et al (2000) but lower than the 39% higher ADG reported for Border Leicester ram compared with wether lambs by Lee (1986b) . Increased gains in ram lambs are associated with male sex hormones such as testosterone ( Kiyma et al, 2000 ) which stimulates increased dietary nitrogen utilization efficiency, an action that is also accompanied by decreased fat deposition ( Judge, 1989 ; Lawrence and Fowler, 1997 ).…”
Section: Discussionsupporting
confidence: 89%
“…The higher growth rates in ram lambs observed in the present study agree with the growth rates found by Lee (1986a) . The 15% higher ADG for ram compared with wether lambs is in close agreement with the results of the studies of Fogarty and Mulholland (2012) and Fogarty et al (2000) but lower than the 39% higher ADG reported for Border Leicester ram compared with wether lambs by Lee (1986b) . Increased gains in ram lambs are associated with male sex hormones such as testosterone ( Kiyma et al, 2000 ) which stimulates increased dietary nitrogen utilization efficiency, an action that is also accompanied by decreased fat deposition ( Judge, 1989 ; Lawrence and Fowler, 1997 ).…”
Section: Discussionsupporting
confidence: 89%
“…According to Haddad, Husein, and Swedan (2006), there was no effect of castration in lambs for HCW, CCW, dressing percentage, or LMA. Fogarty and Mulholland (2012) observed higher for BFT (3.9 mm) in wether lambs when compared with ram animals (2.9 mm). Sales (2014) found that wether lambs had greater dressing percentage and BFT, but LMA was lower when compared with rams.…”
Section: Resultsmentioning
confidence: 84%
“…Lambs fed for a longer period, as expected, had higher carcass weight when compared with animals that spent less time in the feedlot however, with lower feed efficiency ( Table 2). Fogarty and Mulholland (2012) observed that rams had higher body weight at 70 and 170 days of life when compared with females. That resulted in heavier and leaner carcasses.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations